2006
DOI: 10.1677/joe.1.06829
|View full text |Cite
|
Sign up to set email alerts
|

Local over-expression of prolactin in differentiating mouse mammary gland induces functional defects and benign lesions, but no carcinoma

Abstract: Experimental, clinical, and epidemiological data support the growth-promoting role of endocrine prolactin (PRL) in mammary tumors. PRL is also produced by the breast, where it is now recognized to act as a growth/survival factor via autocrine/paracrine mechanisms. Recent transgenic (Tg) mouse models have revealed the pro-oncogenic effect of PRL over-expression in virgin mammary glands. To address the question whether PRL tumorigenicity was maintained on differentiated mammary glands, we generated mammaryspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…While PRL has been described to play a proliferative and tumorigenic role in the mammary epithelium (4,29,32), the overexpression of PRL in the differentiated mammary epithelium resulted in altered alveologenesis, yet no carcinomas were detected (24), suggesting that the state of differentiation of mammary epithelial cells may be an important determinant in specifying the role of PRL as a proliferative agent. While these data indicate that the role of PRL in mammary cell proliferation is complex and requires further investigation, our data indicate that in differentiated mammary epithelial cells, PRL is nonproliferative, and moreover, PRL can attenuate growth factor-induced cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…While PRL has been described to play a proliferative and tumorigenic role in the mammary epithelium (4,29,32), the overexpression of PRL in the differentiated mammary epithelium resulted in altered alveologenesis, yet no carcinomas were detected (24), suggesting that the state of differentiation of mammary epithelial cells may be an important determinant in specifying the role of PRL as a proliferative agent. While these data indicate that the role of PRL in mammary cell proliferation is complex and requires further investigation, our data indicate that in differentiated mammary epithelial cells, PRL is nonproliferative, and moreover, PRL can attenuate growth factor-induced cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, this study failed to reveal whether these morphological anomalies developed into mammary tumors because only young animals were used (24). We recently showed that transgenic mice over-expressing Prl in the differentiating/lactating mammary gland developed various benign lesions from the age of approximately 1 year (25). Using a permanently active promoter, others showed that autocrine Prl induced mammary carcinomas in virgin females from the age of approximately 15 months (26).…”
Section: Discussionmentioning
confidence: 99%
“…Using a permanently active promoter, others showed that autocrine Prl induced mammary carcinomas in virgin females from the age of approximately 15 months (26). Although the mechanisms leading to the development of benign versus malignant tumors are not yet fully understood, they may involve various parameters such as genetic background or the state of differentiation of the gland (25), these studies highlighted the ability of PrlR-triggered pathways to promote mammary tumorogenesis in rodents. In humans, the link between Prl levels and breast carcinogenesis has recently emerged from the Nurse Health study (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their histological differences, the NRL-prolactin-induced tumors tend to belong to the estrogen-resistant luminal subtype of breast cancer (Arendt et al 2011). Interestingly, overexpression of prolactin under the control of whey acidic protein promoter (WAP) does not induce mammary carcinogenesis, suggesting that the differentiation state of cells in which prolactin is overexpressed may influence the ability of prolactin to induce tumorigenesis (Manhes 2006). In addition to initiating transformation by itself, prolactin also cooperates with other prominent regulators of mammary tumorigenesis.…”
Section: Rodent Modelsmentioning
confidence: 99%